Simulating the 21 cm forest detectable with LOFAR and SKA in the spectra of high-z GRBs - Ciardi, B.; Inoue, S.; Abdalla, F.B.; Asad, K.; Bernardi, G.; Bolton, James S.; Brentjens, M.; de Bruyn, A.G.; Chapman, E.; Daiboo, S.; Fernandez, E.R.; Ghosh, A.; et al. (Oxford University Press, 2015)
We investigate the feasibility of detecting 21 cm absorption features in the afterglow spectra of high redshift long Gamma Ray Bursts (GRBs). This is done employing simulations of cosmic reionization, together with estimates of the GRB radio afterglow flux and the instrumental characteristics of the LOw Frequency ARray (LOFAR). We find that absorption features could be marginally (with a S/N larger than a few) detected by LOFAR at z ≳ 7 if the GRB is a highly energetic event originating from Pop III stars, while the detection would be easier if the noise were reduced by one order of magnitude, i.e. similar to what is expected for the first phase of the Square Kilometre Array (SKA1-low). On the other hand, more standard GRBs are too dim to be detected even with ten times the sensitivity of SKA1-low, and only in the most optimistic case can a S/N larger than a few be reached at z ≳ 9.